A simple method for fabricating free-standing large area fluorinated single-layer graphene with size-tunable nanopores. (April 2016) - Wang, Haidong; Kurata, Kosaku; Fukunaga, Takanobu; Takamatsu, Hiroshi; Zhang, Xing; Ikuta, Tatsuya; Takahashi, Koji; Nishiyama, Takashi; Ago, Hiroki; Takata, Yasuyuki
Abstract: As a solid-state membrane with only one-atom thickness, nano-porous graphene has attracted intense attention in many critical applications. Here, the key challenge is to suspend a single-layer graphene (SLG) and drill nanopores with precise dimensions. Here, we report a simple and reliable route for making suspended fluorinated SLG with size-tunable nanopores. Our method consists of two steps: 1. a free-standing SLG ribbon was created between two gold pads after deep dry etching of silicon substrate by xenon difluoride. The SLG was fluorinated by 5–13%. Superior to the normal wet etching method, the dry etching process is much simpler and results in less hole-defect and edge deformation. A large area fluorinated SLG can be suspended due to the sufficient etch depth. 2. a focused ion beam was introduced to drill nanopores in graphene with an initial diameter around 20 nm. Followed by an electron beam induced carbon deposition, the diameter of nanopore was gradually decreased to sub-10 nm. By changing the deposition time, the size of nanopore can be precisely controlled. High-cost transmission electron microscope is no longer needed. Our method provides a simple and effective way for preparing free-standing fluorinated SLG ribbon suitable for single-molecule detection.